Chapter L'azione politica dei sudditi - Provero, Luigi (Reti Medievali E-Book, 2023)
Within a broad and articulated political action of medieval peasant society, the essay aims to identify the specific dynamics relating to Italy in the fourteenth and fifteenth centuries. Through an analysis of the domains of action related to justice, tax collection, frontiers, churches, new villages and clienteles, a specific peasant focus is outlined in the search for effective mediation tools between local society and princely powers.